Co-teaching that works: special and general educators' perspectives on collaboration. Issue 3 (3rd July 2022) - Jortveit, Maryann; Kovač, Velibor Bobo
ABSTRACT: There are surprisingly few studies analysing collaboration between special and general educators that has been proven to work well. The aim of the present study is to explore the perspectives of special and general educators on their collaborative efforts on teaching pupils who receive special education assistance. The study adopts a qualitative approach where interviews with eight educators have been analysed to identify underlying processes and mechanisms that are characteristic of successful collaboration between these two educational professions. The sampling was purposive and only educators who have been found to have achieved successful collaboration in the past were invited to participate. Three main themes emerged during the analysis: a meta-analytic approach to teaching, mutual recognition and enthusiasm, and inclusive education teaching. The overall conclusion of the findings indicates that successful collaboration is embedded in the type of instruction that supports the basic premises of inclusive education and appreciation of diversity. Educational professionals who are willing to come closer to one another in terms of their practice and professional identities are better equipped to succeed in co-teaching situations.